Peningkatan Kemampuan Belajar Anak Berkebutuhan Khusus Dengan Metode Pembelajaran Individual (Studi Kasus : SD Inpres Laikang Kota Makassar) - C, Chaerizanisazi; Ruslan, Risman; Riswal, Muhamad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Increasing the Learning Ability of Children with Special Needs Using Individual Methods Case Study: SD Inpres Laikang. The objectives of this research are: (1) To determine the abilities of children with special needs in accepting forms of learning at SD Inpres Laikang; (2) Knowing the implementation of individual methods in improving the learning abilities of children with special needs at SD Inpres Laikang; (3) Knowing the obstacles and supports found in improving the learning abilities of children with special needs using individual methods at SD Inpres Laikang. This research was carried out in the city of Makassar. It is hoped that the results of this research can obtain data that is in accordance with the individual learning methods of children with special needs at SD Inpres Laikang. This type of research is descriptive qualitative. The research results show an approach that is tailored to the unique needs, abilities and learning styles of each child with special needs, allowing children with special needs to learn according to their own potential and pace in a regular classroom environment. The individual method requires collaboration between teachers and parents to ensure learning needs, self-confidence, encourage acceptance, respect and equal opportunities for all children, including children with special needs, in regular classes.